Pengaruh Permainan Tradisional terhadap Numerasi dan Motivasi Belajar Matematika Peserta Didik Sekolah Dasar - Surya, Anesa; Salimi, Moh; Hidayah, Ratna (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2025)
Numeracy represents a core competency required to navigate the demands of the 21st century. This research aimed to investigate how traditional games influence elementary students’ numeracy abilities and motivation to learn mathematics. This quantitative research involved 60 fourth-grade students from two randomly selected classes in an elementary school in Ngawi Regency, consisting of 30 students in the experimental group (exposed to traditional games) and 30 students in the control group (not given the treatment). Data were collected through numeracy tests (pretest and posttest) and learning motivation questionnaires. The data were analyzed using the Independent Sample t-Test. The findings revealed that: (a) there was a significant effect on numeracy skills in the experimental group after the implementation of traditional game-based learning (t = 5.103, p = 0.000); and (b) there was a significant effect on mathematics learning motivation in the experimental group (t = 6.382, p = 0.000). Therefore, it is crucial for teachers to integrate traditional games effectively as a strategy to enhance numeracy skills and learning motivation in elementary education.